Análisis de los límites éticos de la caricatura política - Moreno Tapia, Anabel Katherine (Machala, 2020)
This research work begins by telling the story of the cartoon, since its emergence in Bologna, in the 16th century. Explain also what is to draw a cartoon and to what extent it is allowed to specify this type of art without violating the rights of third parties, as well as the damages that can be caused to the characters that are drawn. During the time in which this investigation is found, several communication professionals were interviewed, who made sure at some point they were intimidated by the Council for Regulation and Development of Information and Communication (CORDICOM). In this regard, the sources interviewed argued that during the government of former President Rafael Correa, cartoons about the government and its activities could not be published freely, the print media cartoonists suffered prior censorship. Some of the heavy fines received by the cartoonist Xavier Bonilla, aka Bonil, and the newspaper El Universo, where he works, were mentioned. In addition, the interviewees stated that, with the regime change, today there is more freedom to inform and comment on their opinions towards the different social and political events that occur in the country, through the art of political cartoon. Similarly, the interviewees specify that the cartoons do not violate human rights, but that there are specified. Finally, this research paper explains why political authorities and their activities are the main reason for drawing a cartoon.
Este trabajo de investigación empieza contando la historia de la caricatura, desde su surgimiento en Bolonia, en el siglo XVI. Explica también en qué consiste dibujar una caricatura y hasta qué punto es permitido expresar este tipo de arte sin vulnerar los derechos de terceras personas, así como los daños que puede ocasionar a los personajes que están dibujados. Durante el tiempo en que se desarrolló esta investigación se entrevistó a varios profesionales de la comunicación, quienes aseguraron que en algún momento se sintieron intimidados por el Consejo de Regulación y Desarrollo de la Información y la Comunicación (CORDICOM). Al respecto, las fuentes entrevistadas argumentaron que durante el gobierno del ex Presidente Rafael Correa no se podía publicar libremente caricaturas sobre el gobierno y sus actividades, sufriendo censura previa los caricaturistas de medios impresos. Se menciona algunas de las fuertes multas qué recibió el caricaturista Xavier Bonilla, alias Bonil, y el diario El Universo, medio en el cual trabaja. A más de ello, los entrevistados manifestaron que, con el cambio de régimen, hoy en día existe más libertad para informar y expresar sus opiniones hacia los diferentes acontecimientos sociales y políticos que ocurren en el país, a través del arte de la caricatura política. Del mismo modo, los entrevistados mencionaron que las caricaturas no vulneran los derechos humanos, pero que existen excepciones.Finalmente, este trabajo de investigación explica por qué las autoridades políticas y sus actividades son la principal razón para dibujar una caricatura.
Keywords: CARICATURA POLITICA; PRENSA ESCRITA; CARICATURISTA; LIBERTAD DE EXPRESION; MEDIO DE COMUNICACION